Musculação terapêutica no tratamento da condropatia patelar: efeitos do método SCI sobre perímetros musculares, controle articular e sintomas clínicos. - Saulo de Tarso Silva (Revista ft, 2026)
Introduction: Patellar chondropathy is a degenerative condition that generates significant pain and functional limitation. Conventional protocols often fail due to underloading and a lack of individualization. Objective: To evaluate the effects of the SCI Method on muscle circumferences, joint control, and symptoms in patients with patellar chondropathy. Methods: A longitudinal study with men and women (mean age 30–35 years) followed for 24 months. The protocol was based on uni- and bilateral leg extension exercise, a focus on the triceps surae, and muscle stretching, with 100% adapted repetitions and training variables and a consistency exceeding three times per week. Results: A clear resolution of pain was observed (an 89% reduction on the VAS), along with the elimination of edema and functional recovery. All participants achieved over 40 cm on the Sit-and-Reach test (Wells Bench). There was significant thigh hypertrophy (+4.7 cm) and distal stabilization of the calf. Conclusion: The SCI Method proved effective in rehabilitation and structural strengthening, promoting joint stability and the remission of chronic symptoms.